2019
DOI: 10.1155/2019/7573031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonexposed Endoscopic Wall-Inversion Surgery with Endoscopic-Navigated Laparoscopic Wedge Resection for Gastric Submucosal Tumours: Results of a Two-Centre Study

Abstract: Introduction. The aim of this study was to compare the indications, operative details, and clinical outcomes of nonexposed endoscopic wall-inversion surgery with endoscopic-navigated laparoscopic wedge resection of gastric submucosal tumours. Methods. Medical records were reviewed for patients who underwent nonexposed endoscopic wall-inversion surgery (NEWS) at the Faculty Hospital Kralovske Vinohrady and endoscopic-navigated laparoscopic wedge resection (LWR) at the Kepler University Hospital. Demographic, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The main study characteristics are shown in Table 1 [ 14 , 17 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Most of the studies (23) were from Asia (96%) and 22 studies (92%) were single-center.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main study characteristics are shown in Table 1 [ 14 , 17 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Most of the studies (23) were from Asia (96%) and 22 studies (92%) were single-center.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies compared the outcomes of LECS and laparoscopic techniques (4 LECS vs. LWR [ 32 , 37 , 39 , 44 ]; 1 LECS vs. laparoscopic gastrectomy [ 47 ]; 1 LECS vs. LWR and gastrectomy [ 33 ]) in gastric lesions. In meta-analysis, procedure time, hospitalization time, and adverse events were not significantly different between the two groups (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations